Unexpectedly Simultaneous Increase in Wavelength and Output Power of Yellow LEDs Based on Staggered Quantum Wells by TMIn Flux Modulation - Zhenxing Lv; Xiaoyu Zhao; Yuechang Sun; Guoyi Tao; Peng Du; Shengjun Zhou (Nanomaterials, 2022)
Pursuing efficient long-wavelength InGaN LED has been a troublesome issue to be solved, which forms interesting subjects for fundamental research, but finds also motivation in extensive applications. Here, we investigate the effect of TMIn (trimethylindium) flux variation for growing bandgap-engineered staggered quantum wells (QWs) on corresponding LED properties and demonstrate the unexpectedly simultaneous increase in light output power (LOP) and emission wavelength. At 20 mA, LEDs based on staggered QWs grown under low flux show an increase of 28% in LOP and longer wavelength compared to that under high flux. The experimental results reveal that TMIn flux affects crystalline quality and indium composition of epilayers. Under high TMIn flux, high in-plane strain exists between adjacent layers, accompanied by the composition pulling effect, which reduces indium incorporation for the following staggered QW growth and hinders realization of yellow light emission. According to simulation results, low-flux-grown staggered QWs contribute to increased carrier wavefunction overlap as well as enhanced electric field. Notably, the former enables high LOP, while the latter results in emissions towards long wavelength, promising to solve an ever-present concern that LED performance deteriorates with increasing emission wavelength. Therefore, this work shows great significance in thoroughly understanding growth conditions for bandgap-engineered staggered QW structures, which offers a facile solution to achieve efficient long-wavelength optoelectronics devices.